Development of a bivalent protein subunit vaccine against infection by Pseudomonas aeruginosa and Staphylococcus aureus - Suhrid Maiti; Prolay Halder; Debaki Ranjan Howlader; Zackary K. Dietz; Satabdi Biswas; Md. Shafiullah Parvej; Mst. Nusrat Zahan; Ti Lu; Timothy A. Snider; Sean K. Whittier; William D. Picking; Wendy L. Picking (npj Vaccines)
Abstract Pseudomonas aeruginosa (PA) and Staphylococcus aureus (SA) are members of the ESKAPE pathogens, a group of bacteria that are a threat to human health due to their ability to resist antibiotics. They are known to cause severe infections, often as co-morbidities, in individuals with conditions such as people with cystic fibrosis, diabetes, wounds, pneumonia, and critically ill patients requiring intubation leading to ventilator-associated pneumonia. Emergence of multi-drug resistance in SA and PA is making traditional antibiotic treatment ineffective and unfortunately there are no licensed vaccines to prevent MRSA or PA infections. We have demonstrated that when delivered intranasally (IN) L-PaF, a genetic fusion of the PA type III secretion system (T3SS) proteins PcrV and PopB (PaF) with LTA1, the active moiety of heat-labile enterotoxin from enterotoxigenic E. coli, protects against PA. L-PaF was formulated as a nanoemulsion (ME) to increase the protective immune response against clinically relevant PA strains in a mouse lung colonization model. With the addition NEAT2, the heme capturing domain of the SA protein IsdB, a bivalent vaccine was generated. IN administration of the bivalent formulation protected MRSA pre-exposed mice from both MRSA and PA infection. Sera from mice vaccinated with our formulation contained strong IgG titers with high levels of opsonophagocytic killing of homologous and heterologous PA and SA strains. Additionally, the bivalent L-PaF/NEAT2 formulation elicited stimulation of IL-17A and IL-2 cytokines. Because established PA and SA lung infection models with rabbits better reproduce the clinical hallmarks of severe human acute pneumonia, rabbits were immunized with the bivalent L-PaF/NEAT2 formulation. All of the vaccinated rabbits survived the challenges while the controls did not. These findings demonstrate that our L-PaF/ME/NEAT2 formulation has potential as a broad-spectrum vaccine against both SA and PA infection.